2018
DOI: 10.1002/ijc.31779
|View full text |Cite
|
Sign up to set email alerts
|

Thyrocyte‐specific deletion of insulin and IGF‐1 receptors induces papillary thyroid carcinoma‐like lesions through EGFR pathway activation

Abstract: Insulin and insulin-like growth factor (IGF)-1 signaling in the thyroid are thought to be permissive for the coordinated regulation by thyroid-stimulating hormone (TSH) of thyrocyte proliferation and hormone production. However, the integrated role of insulin receptor (IR) and IGF-1 receptor (IGF-1R) in thyroid development and function has not been explored. Here, we generated thyrocyte-specific IR and IGF-1R double knockout (DTIRKO) mice to precisely evaluate the coordinated functions of these receptors in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
(95 reference statements)
0
12
0
Order By: Relevance
“…These processes in turn are mediated through the activities of the sodium iodide symporter and thyroperoxidase, respectively. In a study of mice with conditional double-thyroid knockout of IGF-IR and IR, neonatal thyroid glands were smaller, exhibited repressed FOXE1 expression, and manifested defective folliculogenesis (38). At postnatal day 14, mTORdependent epithelial cell proliferation and serum TSH were detectable.…”
Section: Impact Of Gh and Its Primary Effector Igf-i On The Thyroid Glandmentioning
confidence: 99%
“…These processes in turn are mediated through the activities of the sodium iodide symporter and thyroperoxidase, respectively. In a study of mice with conditional double-thyroid knockout of IGF-IR and IR, neonatal thyroid glands were smaller, exhibited repressed FOXE1 expression, and manifested defective folliculogenesis (38). At postnatal day 14, mTORdependent epithelial cell proliferation and serum TSH were detectable.…”
Section: Impact Of Gh and Its Primary Effector Igf-i On The Thyroid Glandmentioning
confidence: 99%
“…Since NDH patients acquire a wide range of pathologies, including hyperglycemia and hypoinsulinemia, these phenotypes may also affect the development and function of the thyroid gland. This hypothesis is supported by studies showing that the insulin and insulin-like growth factor-1 receptors (INNSR and IGF1R) play a critical role in thyroid folliculogenesis (Ock, et al, 2018) and a GWAS showing the importance of the insulin receptor (INSR) locus in the regulation of thyroid function (Porcu, et al, 2013). The latter study also identified an association between the GLIS3 variant, rs1571583, and the regulation of thyroid dysfunction (Porcu, et al, 2013).…”
Section: Glis3 Mutations and Polymorphisms In Hypothyroidismmentioning
confidence: 77%
“…Similarly, signaling through IGF-1R is essential for normal thyroid formation and function, particularly by supporting thyroid cell survival through TSHR signaling 42,70 . IGF-1R and insulin receptor (IR) double-thyroid knockout mice showed hypoplastic thyroid glands at birth, folliculogenesis defects and specifically repressed Foxe1 expression 71 . Besides, in vitro studies suggest that IGF-1 is required for the differentiation of mouse embryonic stem cells into thyroid epithelial cells, supporting the role of this signal in thyroid development 16,17 .…”
Section: Discussionmentioning
confidence: 99%